The Integration of Knowledge in al-Tafsir al-'Ilmi in Improving the Interpretation Quality of Mutashabihat Verses: An Analysis of Zaghloul Muhammad Raghib El-Naggar's Thought - Habibullah, Ilham; Zubaidi, Sujiat; Chirzin, Muhammad; Nasution, Alhafidh (Universitas Muhammadiyah Surakarta, 2025)
The Integration of Knowledge has become significant in addressing modern scientific developments, particularly the relationship between science and religion, as secular values influence these sciences. Indonesian universities' scientific paradigm tends to focus on theoretical and philosophical foundations. However, al-Tafsir al-'Ilmi, an Islamic study, examines the relationship between religion and science, specifically Qur'anic verses and empirical sciences. This research aims to: reveal the concept of Tafsir al-'Ilmi according to Zaghloul El-Naggar, whose comprehensive approach aligns with modern scientific developments; and uncover the theory of Integration of Knowledge in Tafsir al-'Ilmi according to him. The research employs Syed Mohd Naquib Al-Attas's Integration of Knowledge theory to read Zaghloul El-Naggar's concept philosophically and applicatively. Using qualitative methods, primary, and secondary data analysis, the Integration of Knowledge according to Zaghloul El-Naggar is found to be based on Syed Mohd Naquib Al-Attas's cosmological principles, including tafsir and ta'wil. Muhkamat verses are understood through tafsir, while mutasyabihat verses through ta'wil. The principles of tafsir also apply to understanding natural phenomena, consisting of muhkamat (clear) and mutasyabihat (ambiguous). Al-tafsir al-'ilmi classifies clearly true scientific facts as muhkamat, while theories, hypotheses, and ongoing discoveries are classified as mutasyabihat.